Bromination and iodination of diphosphane dichalcogenides. Issue 8 (8th February 2018) - Upmann, Daniel; Jones, Peter G.
Abstract : Diphosphine dichalcogenides form a variety of adducts with elemental bromine and iodine. Abstract : The diphosphane dichalcogenides dppmSe2, dppeSe2, d i prpmSe2, d i prpeSe2, dppmS2 and dppeS2, [dppm = bis(diphenylphosphano)methane, dppe = bis(diphenylphosphano)ethane, d i prpm = bis(diisopropylphosphano)methane, d i prpe = bis(diisopropylphosphano)ethane] have been treated with elemental bromine or iodine and the products1–15 characterized by single crystal X-ray diffraction. DppeSe2 with bromine or iodine gives the simple (and previously known) adducts dppe(SeBr2 )2 1 or dppe(SeI2 )2 2 respectively; d i prpeSe2 reacts similarly to give d i prpe(SeBr2 )2 3 (at 0 °C) or d i prpe(SeI2 )2 4 . The bromine derivatives display a T-shaped geometry at selenium, whereas the iodine derivatives involve linear Se–I–I groups. With dppmSe2 and bromine, a product was formed at −50 °C, but could not be isolated; at room temperature the reaction leads to a mixture of products, from which only [dppmBr2 ] 2+ [Se2 Br10 ] 2– 5 (the anion involving a dibromine molecule coordinating to a Se centre) could be isolated. Reaction of dppeSe2 with excess bromine at room temperature leads to [dppeBr2 ] 2+ ·½[SeBr6 ] 2– ·[SeBr2 ·Br2 ·Br3 ] − 6 . The reaction of dppmSe2 with iodine gives the 1 : 2 adduct [dppmSe2 I] + [I3 ] − 7, the cation of which contains a novel five-membered CP2 Se2 heterocycle. In a 1 : 1 ratio the same reaction gives another 1 : 2 adduct, [I2 Se(dppm)Se–I–Se(dppm)SeI2 ] + [I3 ] − 8 . D i prpmSe2 with iodine gives [d i prpmSe2 I] + [I3 ] − 9, analogous to7, and with bromine at 0 °C the corresponding product [d i prpmSe2 Br] + [Br3 ] − 10 . At room temperature, d i prpeSe2 reacts with bromine to give a mixture of [d i prpe(SeBr2 )Br] + Br − 11 and [d i prpeBr2 ] 2+ [SeBr4 ] 2– 12, whereas d i prpmSe2 forms [d i prpmBr2 ] 2+ [SeBr4 ] 2– 13, analogous to12 . The disulfides dppmS2 and dppeS2 react with bromine to give [dppmSBr] + [Br3 ] − 14 and [dppeSBr] + [Br3 ] − 15 .